Determination of lead chelated with ethylenediaminetetra-acetic acid in blood after precipitation of protein with perchloric acid - Cernik, A. A. (1970)
Cernik, A. A. (1970).Brit. J. industr. Med.,27, 40-42. Determination of lead chelated with ethylenediaminetetra-acetic acid in blood after precipitation of protein with perchloric acid. A method is described for the determination of lead in whole blood containing ethylene-diaminetetra-acetic acid. Proteins were precipitated by 2·0 m perchloric acid. The ionized lead in the supernatant was chelated with ammonium pyrrolidine dithiocarbamate and was extracted with xylene. The method agreed well with a dry ashing technique (30 samples, correlation coefficient 0·985). Perchloric acid gave consistently good recoveries, unlike trichloroacetic acid, which frequently produced losses of up to 15%.